Peranan Anggaran Biaya Operasional Sebagai Alat Pengendalian Kinerja Manajerial Pada PT. Trans Multi Cargo - Alfin Nathanael; Linda Hetri Suriyanti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study uses a quantitative approach with a survey method. The study population is all managers and supervisors of PT. Trans Multi Cargo who are involved in the operational cost budgeting process, totaling 30 people. The sampling technique uses total sampling (census) so that the entire population becomes the research sample. The data analysis technique uses descriptive analysis and multiple linear regression analysis with the help of SPSS software. The research findings indicate that the operational cost budget has a strategic role as a managerial performance control tool. Comprehensive budget planning, consistent implementation, strict supervision, and continuous evaluation have been proven to significantly improve managerial performance. The results are in line with management control theory which emphasizes the importance of the budget system in achieving organizational goals. The managerial implications of this study are the need for PT. Trans Multi Cargo to continue strengthening the budgeting system as a control tool by improving the quality of budget planning through more in-depth analysis, improving the budget implementation system with better coordination between divisions, optimizing the budget control system through more intensive monitoring, and developing a more comprehensive budget evaluation system for continuous improvement.